Answer: y=-2x+5
Step-by-step explanation:
The measure of angle EBF where he angle measures are given as m∠ABF = (8w − 6)° and m∠ABE = [2(w + 11)] is m∠EBF = 4w - 28
<h3>How to determine the
measure of
angle EBF?</h3>
The angle measures are given as
If m ∠ A B F = ( 8 w − 6 ) ° m ∠ A B E = [ 2 ( w + 11 ) ] ° m ∠ E B F
Rewrite the angle measures properly.
This is done, as follows
m∠ABF = (8w − 6)°
m∠ABE = [2(w + 11)]
The measure of angle m∠EBF is calculated as:
m∠ABF = m∠ABE + m∠EBF
Substitute the known values in the above equation
8w - 6 = 2(2w + 11) + m∠EBF
Open the brackets
8w - 6 = 4w + 22 + m∠EBF
Evaluate the like terms
m∠EBF = 4w - 28
Hence, the measure of angle EBF where he angle measures are given as m∠ABF = (8w − 6)° and m∠ABE = [2(w + 11)] is m∠EBF = 4w - 28
Read more about angles at
brainly.com/question/25716982
#SPJ1
<u>Please</u><u> </u><u>put</u><u> </u><u>a</u><u> </u><u>picture</u><u> </u><u>next</u><u> </u><u>time</u><u> </u><u>:</u><u>)</u>
Answer:
f(n+1) = 13
Step-by-step explanation:
- We know that f(1) = 15
- So we can substitute this for f(n)-3
- With this:
- f(n+1) = f(1) -3
- f(n+1) = 15-2
- f(n+1) = 13